Komposisi, Kelimpahan dan Nilai Ekonomi Ikan Target Di Ekosistem Mangrove Teluk Demta, Kabupaten Jayapura - Muhammad Zulfikarrahman; John Dominggus Kalor; Baigo Hamuna (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
This study aims to determine the diversity, abundance, and economic value of target fish in the mangrove ecosystem of Demta Bay, Jayapura Regency, Papua Province, Indonesia. This research was conducted from August 2019 to January 2020. The research method used was the field observation method, the purposive sampling method, and the method of interviewing the community. The target fish diversity index value at all stations is 1.92. Based on the diversity index criteria it can be seen that the diversity of target fish in the mangrove ecosystem of Demta Bay is classified as moderate. The results of data analysis obtained the value of abundance from all stations is 1086.67. The target fish diversity value and the target fish abundance value indicate that the number of target fish groups in the waters of Demta Bay is quite good. There are several species of target fish that have high prices, namely Ephinephelus quoyanus with the local name Uwga and Cephalopholis microprion with the local name Padamuw. Besides, there are also several species of target fish that have a fairly low selling price, including Pristiapogon fraenatus (Dakai Tipir), Nematolosa come (Pylair), Lactarius lactarius (Lema), Leighnathus equluus (Awara), Valamugil buchanani (Amakai) and Upeneus vittatus (Marep).Keywords: Diversity index; Economic value; Fish target; Demta Bay